-3y -21 +8 = -28
-3y -13 = -28
-3y = -15
y= 5
1: (-1,-1) is (x, y) to see if it is a solution, you would just plug in x and y and see if the equation is true.
-4 (-1) + 2(-1) = 2
4 + -2 = 2
2 = 2 CORRECT
So... plug in x and y in the second equation to Make sure it works for that one too.
-1 + -1 = -2
-2 = -2 CORRECT
So, yes. (-1,-1) is a solution to both equations.
Answer:
Symmetry of functions
A function is an even function if its graph is symmetric with respect to the yyy-axis.
Algebraically, fff is an even function if f(-x)=f(x)f(−x)=f(x)f, left parenthesis, minus, x, right parenthesis, equals, f, left parenthesis, x,
Step-by-step explanation:
MARK ME AS A BRAINLIST
Answer:
2v+2
Step-by-step explanation:
Answer:
No, I don't think so.
Step-by-step explanation: